ANALISIS PENGGUNAAN DIAGNOSIS KEPERAWATAN BERBASIS SDKI DAN NANDA - Nurhesti, Putu Oka Yuli; Prapti, Ni Ketut Guru; Kamayani, Made Oka Ari; Suryawan, Putu Adi (Coping: Community of Publishing in Nursing; Vol 8 No 2 (2020): Agustus 2020DO - 10.24843/coping.2020.v08.i02.p02, 2020)
Nursing care is a scientific method in the development of the scientific nursing body of knowledge. Nursing care is a means of developing the discipline of nursing and nursing practice that characterizes nursing and distinguishes the nursing profession and other professions. This development can be done continuously through nursing research. SDKI and NANDA are the two diagnostic standards used in the provision of nursing care in Indonesia. The ability of nurses to perform the nursing diagnosis stage in nursing care is very important because it will influence the stage of goal setting and intervention as well as evaluation and documentation. The general objective of this study was to determine the differences in the application of nursing diagnoses with the SDKI and NANDA which are diagnostic standards that have been applied internationally. This was a comparative study, which uses both the outpatient and inpatient case settings for the application of nursing diagnoses at Udayana University Hospital. The sample for each group used 30 cases. The results show there are differences in ease, clinical reasoning, and diagnostic comprehension based on the SDKI and NANDA. There is no difference in nursing diagnoses in the language context of diagnosis between the SDKI and NANDA. Both diagnosis standards can be used as a reference in nursing care in a hospital. Differences in diagnosis raised only in the use of language individually Keywords: nursing diagnosis, SDKI, NANDA